Composite Confidence Estimators for Enhanced Speculation Control - Jimenez, Daniel A. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2009)
This paper proposes a way to allow more effective use of speculation control techniques by combining multiple confidence estimators into a {em composite confidence estimator}. This new class of confidence estimators provides improved performance and finer speculation control. This paper makes three contributions. First, we describe techniques for building efficient composite confidence estimators. Second, we present an improved statistical methodology for evaluating confidence estimators. Finally, we use a detailed microarchitectural simulator to evaluate the ability of our estimator to support an energy reduction technique called pipeline gating. Using previous confidence estimators, pipeline gating reduces the amount of extra work due to mis-speculated instructions by 22%, with a reduction in IPC of 5%. With the same impact on IPC, our confidence estimators reduce extra work by 31%.